CHRONOLOGY OF FOSSILIFEROUS LOCALITIES IN MANJRA VALLEY, DISTRICT LATUR, MAHARASHTRA, INDIA. Issue 2 (8th April 2022) - Sathe, Vijay; Kumar, Pankaj; Chakraborty, Prateek; Sharma, Rajveer
ABSTRACT: The present paper is an announcement of first absolute age dating directly on fossilized bones and teeth of the Pleistocene mammalian fauna from the Manjra valley, District Latur, Maharashtra, India. The fossilized samples were measured using the AMS facility at Inter-University Accelerator Centre, New Delhi, India. The results gave the time frame of 21, 423 BP to 24, 335 BP that correspond close to and the threshold of LGM and sheds important light on the palaeoecology of the area that supported diverse megafaunal species in the Upper Manjra valley. These calendar dates not only have wider significance in terms of first ever approximate chronological frame for the Pleistocene fauna in Peninsular India but also offer methodological innovations especially when the adequate bioapatite is absent in the fossilized bones and teeth from the fossil record.